Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 7 - Exponents and Exponential Functions - 7-5 Division Properties of Exponents - Practice and Problem-Solving Exercises - Page 446: 91



Work Step by Step

Given : $(\frac{x^{n}}{x^{n-2}}$$)^{3}=$ $(x^{n-(n-2)})^{3}=$ $(x^{n-n+2})^{3}=$ $(x^{2})^{3}=$ $x^{6}$ Since $\frac{a^{m}}{a^{n}}=$ $a^{m-n}$ and $(a^{m})^{n}=$ $a^{mn}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.